Efficacy of atomoxetine in children with severe autistic disorders and symptoms of ADHD: An open-label study - Chawanun Charnsil (2018)
Objective: This study aims to examine the efficacy of atomoxetine in treating symptoms of attention deficit hyperactivity disorder (ADHD) in children with severe autistic disorder. Method: Children with severe autistic disorder who had symptoms of ADHD were given atomoxetine for 10 weeks. The efficacy of atomoxetine was evaluated by using the Aberrant Behavior Checklist (ABC) to rate ADHD symptoms at baseline, week 6, and week 10. The Clinical Global Impression-Improvement (CGI-I) scale was used as secondary outcome to assess the overall improvement of the children's development at week 10. Results: A total of 12 children participated in this study. Although CGI-I scores showed improvement at week 10, the ABC hyperactivity subscale did not show a significant improvement of the ADHD symptoms at baseline (M = 33.89) compared to those at week 10 (M = 31.78, p = .62). Conclusion: Atomoxetine did not benefit children with severe autistic disorder who have ADHD symptoms. © 2011 SAGE Publications.